Safer in School? The Impact of Compulsory Schooling on Maltreatment and Associated Harms - Dzulkipli, Adam A.; Black, Nicole; Johnston, David W.; Segal, Leonie (The Review of Economics and Statistics, 2025)
Abstract Abused and neglected children are at extreme risk of school dropout, poor health, and destructive behaviours, yet evidence on interventions that prevent maltreatment and its harms is limited. We use a South Australian education reform to examine whether extending the school-leaving age from 16 to 17 improves maltreatment-related outcomes. Using administrative records and regression-discontinuity techniques, we find that the reform reduced first-time cases of maltreatment reported to Child Protection Services (CPS). Among adolescents with past CPS involvement, it also reduced emergency healthcare utilisation. Our findings suggest school attendance can improve child safety, with an incapacitation effect as the likely mechanism.